What is the evidence for and validity of return-to-sport testing after anterior cruciate ligament reconstruction surgery? A systematic review and meta-analysis - Webster, K. E.; Hewett, T. E. (Sports Medicine, 2019)
Background: Anterior cruciate ligament (ACL) return-to-sport (RTS) test batteries are popular and are employed to test athletes` sport performance and help ensure a safe return to sport. Objective: To perform a systematic review and meta-analysis to determine: (1) the proportion of patients who passed RTS test batteries after ACL reconstruction, (2) whether passing RTS test batteries increased rates of return to play, and (3) whether passing RTS test batteries reduced subsequent rates of knee and ACL injury. Methods: Five databases (PubMed, MEDLINE, Embase, CINAHL, and SPORTDiscus) were searched to identify relevant studies and data were extracted regarding the number of patients who passed the RTS test battery, as well as subsequent RTS rates and re-injury data when available. Results were combined using proportional and risk-ratio meta-analyses. Results: Eighteen studies met eligibility criteria. Proportional meta-analysis showed that only 23% of patients passed RTS test batteries. One study showed that passing an RTS test battery led to greater RTS rates. Two studies showed passing RTS test batteries did not significantly reduce the risk of a further knee injury (risk ratio (RR) = 0.28 (95% CI 0.04-0.94), p = 0.09) and five studies showed that passing RTS test batteries did not reduce the risk for all subsequent ACL injuries (RR = 0.80 (95% CI 0.27-2.3), p = 0.7). However, passing an RTS test battery did significantly reduce the risk for subsequent graft rupture (RR = 0.40 (95% CI 0.23-0.69), p < 0.001], although it increased the risk for a subsequent contralateral ACL injury (RR = 3.35 (95% CI 1.52-7.37), p = 0.003]. Conclusion: These analyses shows that there are equivocal findings in terms of the validity of current RTS test batteries in relation to reduction of the risk of graft rupture and contralateral ACL injuries. These findings have implications for RTS advice given to patients based on the results of RTS test batteries, and further work is needed to validate the criteria currently used and determine the true value.